Exploring Transitions: Young Adult Development From A Psychological Perspective - Khairatunnimah. SM; Eva Latipah (Yayasan Adra Karima Hubbi, 2024)
This research aims to describe the development of young adults from a psychological perspective. This research uses literature review research, namely conducting library searches and research by reading various kinds of books, journals and other library publications related to the topic under study. Data analysis techniques used in this research is a content analysis method. Meanwhile, the data sources used are books and research journals. The results of this research are that early adulthood is also known as the transition from adolescence to adulthood, which occurs approximately between the ages of 20 and 40 years. The transition from dependence on others to independence, both in terms of economics, freedom of self-determination, and views of the future, as well as changes in physical, intellectual, social roles, psychology, and reproductive abilities. However, early adulthood is considered an immature age in terms of social relationships, because the busyness of pursuing a career, working, getting married, and involvement in activities outside the home decreases. As a result, early adult individuals will experience social isolation for the first time, this is known as a competitive crisis by Erickson.